Aktivitas Ekstrak Etanol Daun Akar Kucing (Acalypha indica L.) Sebagai Pengawet Alami Pada Buah Tomat (Lycopersium esculentum Mill.) - Solichah, Ayu Ina; Sawal, Rizky Ardian Hartanto; Auliya, Fitri (Jurnal Farmasi & Sains Indonesia, 2023)
The presence of preservatives in food is a common thing to extend the shelf life of foods. The bad effects appliying chemical preservatives cause both environmental pollution and health disturbing. Consuming chemical preservatives for a long time will will cause cancer. Natural preservatives is needed to reducing the bad effects. One of the Plants can be applied as natural preservatives is cat root leaves (Acalypha indica L. The study aims were to determine the activity and effective concentration of cat root leaf extract as a natural preservative on tomatoes and to identify the its phytochemical content. Activity of cat root leaf extract as a preservative was subjected by organoleptic, meanwhile the phytochemical content by tube-test. The results showed 8% cat root leaf extract effective as natural preservative according to organoleptic observation with observed time for 20 days. The result of tube-test showed cat root leaf extract contain compounds likes alkaloid, flavonoid, saponin, tannin, and terpenoid.